5PSQ-007 The pharmaceutical governance of low molecular weight heparins: appropriateness analysis. (24th March 2020) - Garreffa, MR; Vitale, P; De Franco Iannuzzi, A
Abstract : Background and importance: Since 2017, in our region, low molecular weight heparins (LMWH) used off-label for prophylaxis and the treatment of venous thromboembolism in pregnancy, oncology and for bridging therapy (bridging therapy in patients who must suspend antivitamin K drugs for surgical manoeuvres) are supplied by private pharmacies on behalf of the local health authority (LHA). Aim and objectives: To verify the economic and clinical impact of the new regional provisions on our health district. Material and methods: We evaluated LMWH prescriptions (ATC B01AB) paid to the National Health Service (NHS) of our health district (about 164 000 inhabitants) related to the period January 2017 to December 2018. We analysed consumption in terms of packages, DDD×1000ab/day and spending using an electronic worksheet. Results: The number of treated patients (10 535) decreased by 33.35% from January 2017 to December 2018. Implementation of the new distribution modality of off-label LMWH led to a decrease in the number of packs supplied by the traditional distributor (−68.80%) compared with a marked increase (+428%) in those supplied by private pharmacies on behalf of the LHA. Patients who received prescriptions for heparins off-label tripled in 2018 compared with 2017; the DDD×1000ab/day decreased by 67.50% for traditional distributors and increased by >500% for private pharmacies. This led to an important reduction in costs for the NHS, with a decrease in the cost of LMWH of 72.63% in our territory. Conclusion and relevance: The significant increase in off-label LMWH prescriptions carried out following the preparation of a therapeutic plan made it possible to strengthen the monitoring of prescriptions as the indication for which the drug was suggested must be highlighted by reporting specific codes on the prescriptions. The renegotiation of the prices of drugs provided by private pharmacies on behalf of the LHA is part of a pharmaceutical governance plan that results in a reduction of costs in favour of the patient's health, as demonstrated by our study. References and/or acknowledgements: No conflict of interest.